Morphology, histology and histochemistry of the digestive system of south american catfish (Rhamdia quelen) - Hernández, David Roque (2009)
Fil: Hernández, David Roque. Universidad Nacional del Nordeste. Facultad de Ciencias Veterinarias; Argentina.